THE ANALYSIS OF SECONDARY EMOTION TOWARD CLOTHILDE DESTANGE’S CHARACTER IN THE BLONDE LADY NOVEL BY MAURICE LEBLANC - Lusi, Monica; Kuncara, Singgih Daru; Setyowati, Ririn (Fakultas Ilmu Budaya Universitas Mulawarman, 2019)
ABSTRACT The study of emotion is interesting and unique to be understood and discussed. Moreover, analysis about emotion in the novel is challenging because it cannot be analyzed by facial expression of the character but based on the narration and the dialogue of the character. The purposes of this study are to analyze the secondary emotions and the factors that cause it toward Clotilde Destange’s Character in The Blonde Lady novel by Maurice LeBlanc. Ten Houten’s present theory from Plutchik about secondary emotion was suitable to be used as the theory to identify the secondary emotions that are appears in the Clotilde’s Character and the theory from Plutchik about emotion as a chain of event to examine the factors that cause secondary emotion of Clotilde’s character. The qualitative method was used to analyze the novel. This research uses sentences, pages, narration, dialogues, and paragraph that related to the secondary emotion in The Blonde Lady novels. The results of the study show that the secondary emotion appeared in the main female character. The study also was identified that the factors that cause the secondary emotion of Clotilde’s character is come from the stimulus event which followed by cognition, feeling states, overt behavior. Stimulus event in here act as the actor who has a role to start the emotion process going. Moreover, the stimulus event did not only come from the main female character itself but also came from other main characters which affected the main female character in expressing her secondary emotion. Keywords: emotion, secondary emotion ABSTRAK Penelitian mengenai emosi itu menarik dan unik untuk dipahami dan dibahas. Selain itu, analisis mengenai emosi didalam novel itu sangat menantang karena emosi tidak bisa dianalisa dengan ekspresi wajah karakter namun berdasarkan dari narasi dan dialog dari karakter. Tujuan dari penelitian ini adalah untuk menganalisa mengenai emosi sekunder dan faktor penyebabnya terhadap karakter Clotilde Destange di dalam novel, The Blonde Lady oleh Maurice LeBlanc. Teori baru TenHouten dari Plutchik tentang emosi sekunder cocok untuk digunakan sebagai teori untuk mengidentifikasi emosi sekunder yang muncul dalam karakter Clotilde dan teori dari Plutchik tentang emosi sebagai rangkaian peristiwa untuk memeriksa faktor-faktor yang menyebabkan emosi sekunder dari karakter Clotilde. Metode kualitatif digunakan untuk menganalisis novel. Penelitian ini menggunakan kalimat, halaman, narasi, dialog, dan paragraf yang terkait dengan emosi sekunder dalam novel The Blonde Lady. Hasil penelitian menunjukkan bahwa emosi sekunder muncul pada karakter wanita utama. Penelitian ini juga mengidentifikasi bahwa faktor-faktor yang menyebabkan emosi sekunder karakter Clotilde berasal dari peristiwa stimulus yang diikuti oleh kognisi, keadaan perasaan, perilaku terbuka. Peristiwa stimulus di sini bertindak sebagai aktor yang memiliki peran untuk memulai proses emosi. Selain itu, peristiwa stimulus tidak hanya berasal dari karakter utama wanita itu sendiri tetapi juga berasal dari karakter utama lainnya yang mempengaruhi karakter utama wanita dalam mengekspresikan emosinya. Kata kunci: emosi, emosi sekunder